APPLICATION OF BLOCKCHAIN TECHNOLOGY IN THE TAXATION SYSTEM: BENEFITS AND RISKS - Gunawan Widjaja (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The application of blockchain technology in the tax system offers opportunities to improve the transparency, security, and efficiency of tax data management. With its decentralised and immutable nature, blockchain minimises the risk of fraud and manipulation, and reduces the potential for tax evasion. However, there are also a number of challenges and risks to be faced, including dependence on technology and cybersecurity threats. In addition, regulatory updates are required to accommodate the use of this technology. Overall, if implemented appropriately, blockchain can revolutionise the tax system, support fiscal justice, and increase public participation in tax obligations.